Community-Acquired Antibiotic Resistance in Urinary Isolates from Adult Women in Canada. Issue 6 (1st December 2006) - McIsaac, Warren J; Mazzulli, Tony; Permaul, Joanne; Moineddin, Rahim; Low, Donald E
Abstract : BACKGROUND: There are currently limited data regarding the prevalence of antimicrobial-resistant organisms causing community-acquired urinary tract infections among adult women in Canada. Trimethoprim-sulfamethoxazole (TMP-SMX) is the recommended first-line empirical antibiotic treatment, unless resistance of Escherichia coli to TMP-SMX exceeds 20%. OBJECTIVE: To assess current levels of TMP-SMX-resistant E coli in community-acquired cases of urinary tract infection in adult women. METHOD: Assessment of urine culture reports obtained from 21 laboratories across Canada, submitted by family physicians for women aged 16 years and older. RESULTS: In 2199 adult women with a positive urine culture, 1079 (49.1%) of pathogens isolated were resistant to at least one antibiotic and 660 (30.0%) were multidrug-resistant (resistant to two or more antibiotics). TMP-SMX resistance was seen in 245 of 1613 (15.2%) E coli isolates (95% CI 13.5 to 17.0). This proportion was higher in women 50 years of age and older (155 of 863 isolates [18.0%]; P=0.001), in British Columbia (70 of 342 isolates [20.5%]) and in Ontario (62 of 370 isolates [16.8%]) when compared with eastern provinces (65 of 572 isolates [11.4%]; P=0.001). Fluoroquinolone-resistant E coli occurred in 107 of 1557 (6.9%) isolates (95% CI 5.7 to 8.2), with the highest level found in British Columbia (54 of 341 isolates [15.8%]; P=0.001). CONCLUSION: TMP-SMX continues to be appropriate as first-line empirical treatment of acute cystitis in adult women in Canada, as resistance remains below 20%. However, TMP-SMX resistance is higher in older women and in some provinces. The level of fluoroquinolone-resistant E coli is highest in British Columbia.